Pembiayaan Bermasalah dan Pertumbuhan Bank Muamalat Indonesia: Peran Kecukupan Modal Sebagai Pemoderasi - Ani Rahmawati; Supriyanto Supriyanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study examines the relationship between financing quality and the financial performance of Bank Muamalat Indonesia by analyzing non-performing financing (NPF), capital adequacy (CAR), and inflation. Using 43 quarterly financial reports from 2015 to 2025, data were analyzed via PLS-SEM with SmartPLS 3, employing 10,000-subsample bootstrapping and a Two-Stage Approach. Results indicate that rising NPF is associated with declining asset growth (β = −0.509; p = 0.012), while its relationship with revenue growth is not significant (p = 0.230). Capital adequacy reinforces the negative association with asset growth (β = −0.418; p = 0.032), but shows no significant link to revenue growth (p = 0.943). Inflation demonstrates a positive and significant relationship with both asset and revenue growth. The model explains 40.6% of the variance in asset growth and 20.0% in revenue growth. Strong capital positions appear to make banks more cautious in financing disbursement when NPF rises. Strengthening financing selection and optimizing capital utilization can support more stable bank performance growth.